Students’ Mispronunciation On English Vowels In Reading Aloud For Senior High School - Moh Fathoni; Khoirunnisa, Maula; Andanty, Ferra Dian (Journal of Applied Linguistics and English Education, 2024)
This study is about analyzing students' pronunciation abilities. The researcher analyzed pronunciation errors in English vowels produced by male and female students in grade 2 at SMAN 1 Menganti, Gresik Regency. This study aims to find pronunciation errors in English vowels produced by these students. The method used was qualitative descriptive. The data source in this study was 24 students in class X1 IPA 3 SMAN 1 Menganti, Gresik Regency, consisting of 7 male students and 17 female students. Data collection was carried out by conducting a reading aloud test. The results of this study indicate that students at SMAN 1 Menganti, Gresik Regency, often make pronunciation errors in the vowels: /ә/, /æ/, /ε/, /з:/, and /Λ/.